MUTYH‐associated polyposis – colorectal phenotype and management. (18th May 2020) - Patel, R.; McGinty, P.; Cuthill, V.; Hawkins, M.; Moorghen, M.; Clark, S. K.; Latchford, A.
Abstract: Aim: The aim was to determine the presentation, management and outcomes of MUTYH ‐associated polyposis (MAP). Method: A prospectively maintained database was used to identify patients with MAP. Demographic data and data on germline mutation, surgical management, histopathology of tumours and endoscopic surveillance were collected. Results: In all, 134 patients with MAP were identified. The majority presented symptomatically ( n = 83). Sixty‐eight patients developed cancer (seven synchronous, 12 metachronous). The median age at diagnosis of first colorectal cancer was 47 years (range 33–74 years). Cancers occurred in the context of a few adenomas (< 10). The majority of patients ( n = 108) had surgery as the first line management. One patient received palliative care. Twenty‐five patients had endoscopic surveillance as first line management; no cancers occurred in this group. Patients who had segmental resection and postoperative surveillance still appeared to be at risk of metachronous cancer (5/30, 17%). Conclusions: MUTYH testing should be considered even in the context of cancers occurring with fewer than 10 adenomas. In cases of primary colorectal cancers, extended surgery should be considered if patients do not have access to high quality endoscopic surveillance postoperatively. For some patients, endoscopic therapy is an appropriate and safe option in expert hands.